Response to neoadjuvant treatment among rectal cancer patients in a population-based cohort - Alwers, Elizabeth; Jansen, Lina; Kather, Jakob Nikolas; Amitay, Efrat L.; Bläker, Hendrik; Kloor, Matthias; Tagscherer, Katrin; Roth, Wilfried; Herpel, Esther; Chang-Claude, Jenny; Brenner, Hermann; Hoffmeister, Michael (International journal of colorectal disease, 2021)
In rectal cancer, prediction of tumor response and pathological complete response (pCR) to neoadjuvant treatment could contribute to refine selection of patients who might benefit from a delayed- or no-surgery approach. The aim of this study was to explore the association of clinical and molecular characteristics of rectal cancer with response to neoadjuvant treatment and to compare patient survival according to level of response.
Online publiziert: 19. September 2020
Gesehen am 17.09.2025